Quinoline alkaloids with anti-inflammatory activity from Zanthoxylum avicennae. Issue 20 (10th May 2022) - Ji, Kai-Long; Liu, Wei; Yin, Wei-Hang; Li, Jing-Ya; Yue, Jian-Min
Abstract : Ten quinoline alkaloids from Zanthoxylum avicennae, of which 1 possesses an unusual structure and 6 exhibits anti-inflammatory effect in macrophages. Abstract : Zanthoxylum avicennae fruits were traditionally used to treat many inflammatory-related diseases, such as icterohepatitis, nephritis and colitis, which inspired us to explore the active chemicals and pharmacological activity. As a result, ten quinoline alkaloids, including six new ones, avicenines A–F (1–6 ), were isolated and structurally characterized by solid data. Compounds 1, 7 and 8 were identified as three pairs of enantiomers by chiral HPLC separation, of which 1 was an unusual 6/6/5/5-fused quinoline alkaloid bearing a unique cis -hexahydrofuro[3, 2- b ]furan moiety. The putative biosynthetic pathway for enantiomeric compounds was also proposed. In addition, compound 6 significantly suppressed the gene expression and secretion of pro-inflammatory cytokines IL-1β and IL-6 in macrophages.